2013
DOI: 10.3109/09537104.2013.827782
|View full text |Cite
|
Sign up to set email alerts
|

The pretreatment platelet and plasma fibrinogen level correlate with tumor progression and metastasis in patients with pancreatic cancer

Abstract: Cancer patients frequently present with activated coagulation pathways and thrombocytosis, which are potentially associated with tumor progression and prognosis. However, the prognostic value of abnormal plasma fibrinogen and platelet levels for the treatment of pancreatic cancer is unclear. The purpose of our study was to evaluate the prognostic value of plasma fibrinogen and platelet levels in pancreatic cancer, and to devise a prognostic model to identify the patients with greatest risk for a poor overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 29 publications
7
66
0
Order By: Relevance
“…We found that the incidence of thrombocytosis was 8.5% (20/234) in stage I NSCLC patients. This result was consistent with the previous studies in gastric cancer (11.4%) [22], rectal cancer (8%) [23] and pancreatic cancer (15.2%) [24]. Elevated platelet count was related with NSCLC differentiation and T stage.…”
Section: Discussionsupporting
confidence: 95%
“…We found that the incidence of thrombocytosis was 8.5% (20/234) in stage I NSCLC patients. This result was consistent with the previous studies in gastric cancer (11.4%) [22], rectal cancer (8%) [23] and pancreatic cancer (15.2%) [24]. Elevated platelet count was related with NSCLC differentiation and T stage.…”
Section: Discussionsupporting
confidence: 95%
“…In the present study, baseline hyperfibrinogenemia tended to be associated with late clinical stage, older age, and high PS. These findings are in accordance with previously published data for other malignancies [16][17][18], reflecting the suspicion that fibrinogen is involved in the progression and metastasis of BTC during the late phase of disease.…”
Section: Discussionsupporting
confidence: 94%
“…However, a convenient and dynamic means of monitoring clinical response or predicting prognosis has yet to be established. Recently, links between hyperfibrinogenemia and malignancies such as breast, gastric, lung, colorectal, pancreatic, and endometrial cancers have been increasingly recognized [14][15][16][17][24][25][26]. A previous retrospective study demonstrated that the preoperative plasma fibrinogen level was an independent marker of poor prognosis in gallbladder cancer patients following surgical resection [19]; however, no data have been reported on the clinicopathological and prognostic value of baseline plasma fibrinogen concentrations in patients with BTC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A complete blood count was regularly taken, and thrombocytosis was defined as platelet count greater than 300 Â 10 9 /L. 36 …”
Section: D-dimer Fibrinogen and Platelet Measurementmentioning
confidence: 99%